Hubungan Macam Rujukan Dengan Keluaran Maternal Dan Neonatal - Leri Septiani; Lina Herlina (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
The increasing maternal and neonatal mortality rate is partly due to delays in emergency obstetric referrals. The referral system plays a crucial role in early detection of high-risk maternal outcomes to prevent fatal complications. This study aimed to determine the factors associated with maternal neonatal outcomes using LBPR and the success of the referral system at the Ciasem Community Health Center, Subang Regency. An observational cross-sectional study using a non-probability total sampling method was conducted on 47 women who were pregnant, in labor, or experiencing an obstetric emergency postpartum. After collecting data from surveys and medical records, the chi-square test was used for analysis. Maternal neonatal outcomes were associated with the type of referral, as indicated by an Asymp.Sig value of 0.000 < 0.05. Respondents' awareness of health workers' recommendations was also high, supporting the role of LBPR in optimizing emergency care. It was concluded that the use of LBPR is effective in early high-risk detection, increases referral success, and has the potential to reduce maternal and infant mortality.